rasiRNA pathway controls antisense expression of Drosophila telomeric retrotransposons in the nucleus. - Shpiz, S.; Kwon, D.; Rozovsky, Y.; Kalmykova, A. (Nucleic Acids Research, 2009)
Telomeres in Drosophila are maintained by the specialized telomeric retrotransposons HeT-A, TART and TAHRE. Sense transcripts of telomeric retroelements were shown to be the targets of a specialized RNA-interference mechanism, a repeat-associated short interfering (rasi)RNA-mediated system. Antisense rasiRNAs play a key role in this mechanism, highlighting the importance of antisense expression in retrotransposon silencing. Previously, bidirectional transcription was reported for the telomeric element TART. Here, we show that HeT-A is also bidirectionally transcribed, and HeT-A antisense transcription in ovaries is regulated by a promoter localized within its 3' untranslated region. A remarkable feature of noncoding HeT-A antisense transcripts is the presence of multiple introns. We demonstrate that sense and antisense HeT-A-specific rasiRNAs are present in the same tissue, indicating that transcripts of both directions may be considered as natural targets of the rasiRNA pathway. We found that the expression of antisense transcripts of telomeric elements is regulated by the RNA silencing machinery, suggesting rasiRNA-mediated interplay between sense and antisense transcripts in the cell. Finally, this regulation occurs in the nucleus since disruption of the rasiRNA pathway leads to an accumulation of TART and HeT-A transcripts in germ cell nuclei.